1997
DOI: 10.1002/(sici)1097-0193(1997)5:6<422::aid-hbm3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual attention assessed with PET

Abstract: Brain mechanisms involved in the maintenance of attention to auditory and visual stimuli at different spatial locations were assessed using positron emission tomography with [15O]water to measure regional cerebral blood flow (rCBF) changes in 13 normal volunteers. Simultaneous auditory [dichotically presented consonant-vowel-consonants (CVCs)] and visual stimuli (vertically oriented, CVCs presented to the left and right of fixation) were presented on every trial. In different conditions subjects attended for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 31 publications
5
14
0
Order By: Relevance
“…This general attentional effect is consistent with numerous auditory ERP studies (Hillyard et al, 1973;Woldorff et al, 1993; as well as with prior imaging studies using various speech (Grady et al, 1997;Hashimoto et al, 2000;Hugdahl et al, 2000;Hugdahl et al, 2003;Jancke et al, 2001;Jancke et al, 1999;O'Leary et al, 1997;Pugh et al, 1996;Vingerhoets & Luppens, 2001) and nonspeech (Hall et al, 2000;Jancke et al, 2003) auditory stimuli. Contrasts emphasizing speech sound processing (Speech-Rotated) and lexical processing (Word-Pseudoword) showed not only main effects of these stimulus variables but also strong interactions between attention and stimulus type.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This general attentional effect is consistent with numerous auditory ERP studies (Hillyard et al, 1973;Woldorff et al, 1993; as well as with prior imaging studies using various speech (Grady et al, 1997;Hashimoto et al, 2000;Hugdahl et al, 2000;Hugdahl et al, 2003;Jancke et al, 2001;Jancke et al, 1999;O'Leary et al, 1997;Pugh et al, 1996;Vingerhoets & Luppens, 2001) and nonspeech (Hall et al, 2000;Jancke et al, 2003) auditory stimuli. Contrasts emphasizing speech sound processing (Speech-Rotated) and lexical processing (Word-Pseudoword) showed not only main effects of these stimulus variables but also strong interactions between attention and stimulus type.…”
Section: Discussionsupporting
confidence: 89%
“…This approach produces larger selection effects compared with the within-modality selective attention paradigm (i.e., dichotic listening) (Duncan et al, 1997;Rees et al, 2001;Treisman, 1973). Functional imaging studies using this paradigm showed increased activation in brain regions implicated in processing of the attended modality (Johnson & Zatorre, 2005;O'Leary et al, 1997;Woodruff et al, 1996). Petkov and colleagues examined BOLD activations in the auditory cortex to unattended tones during a primary visual task and by the same tones when attended (Petkov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal lobe auditory regions that have consistently shown robust activation during the dichotic task in our laboratory (O'Leary et al 1996(O'Leary et al , 1997, and in others' (Hugdahl et al1999(Hugdahl et al , 2000, did not show rCBF increases that were significantly different from a baseline condition. Additionally, marijuana decreased rCBF in comparison to the baseline condition in brain regions that have been found in a number of studies to be involved in attentional modulation of sensory processing (Chelazzi and Corbetta 2000).…”
Section: Discussionmentioning
confidence: 47%
“…3 The auditory discrimination task was associated with increased cerebral activity in the right superior/middle temporal gyrus (BA 21/22) and the inferior occipital cortex bilaterally (BA 18), while the visual discrimination task was associated with increased cerebral activity in the right superior parietal (BA 7), angular gyrus (BA 39), occipital regions (BA 19), and right fusiform (BA 20). These cerebral areas had previously been found to be associated with sensory discrimination processes [6,18,37,42,57]. 4 We were interested in finding out whether dual-task management involves supplementary activity at the level of the prefrontal cortex (e.g., [20,31]) or more activity only in the posterior cerebral areas already activated by the single tasks (e.g., [10]).…”
Section: Discussionmentioning
confidence: 99%
“…However, at P < 0.001 uncorrected, foci of activity were observed bilaterally in the superior parietal gyrus for the visual task as well as in the right superior/middle temporal gyrus (BA 21/ 22) for the auditory task and in the right middle and superior occipital (BA 19) (see Table 2). Previous work exploring visual and auditory information processing demonstrated activity in these areas [6,37,42],…”
Section: Single Tasks Minus Baselinementioning
confidence: 99%